An audit system for regulatory authorities and professional bodies to assess the operational competence of occupational hygiene approved inspection authorities - Bosch, Conrad (My University, 2009)
ABSTRACT In South Africa the assessment of exposure to occupational hygiene stressors or environmental factors in workplaces covered by the Occupational Health & Safety Act, Act No. 85 of 1993 must be performed or at least verified by an Approved Inspection Authority for occupational hygiene. However, no formal system is in place to effectively audit and score operational work of Approved Inspection Authorities for occupational hygiene. Formal auditing is a requirement of internationally accepted and implemented management systems such as the International Standards Organisation (ISO) 9001: 2000, Quality Management System – Requirements, the British Standards Institution - Occupational Health and Safety Series (OHSAS) 18001: 1999, as well as the International Standard - ISO 14000: 2004: Environmental Management System. To develop an audit system for Approved Inspection Authorities for occupational hygiene, a descriptive research project that gathered relevant data through electronic questionnaires was conducted with the objective of identifying audit elements and a general scoring system as well as the development of an audit tool that can be applied by regulatory authorities, professional bodies and even competent persons to audit operational work of Approved Inspection Authorities for occupational hygiene. 5 This study had a sample population of 40 Approved Inspection Authorities for occupational hygiene, all based in the Gauteng Province, the province which had the largest number of Approved Inspection Authorities for occupational hygiene. A questionnaire was compiled from local and international audit elements and emailed to the study population for electronic completion. The cover letter and study questionnaire is appended as ANNEXURE A and ANNEXURE B respectively. The Ethics Committee – Clearance Certificate is appended as ANNEXURE C. The questionnaire listed the proposed audit elements and a number of questions relating to the registration of the Approved Inspection Authority for occupational hygiene. A scoring mechanism was also suggested. Questions asked in the questionnaire applied the equivalent-form approach whereby as far as reasonably practicable each question was rephrased so that it “appeared different”, but effectively asked the same question. The study had a response rate of 65%, or a total of twenty six returned questionnaires. The respondents were in agreement that the elements; Organisation & Administration, Human Resources, Accommodation & Environment, Equipment, Measurement & Testing as well as Occupational Hygiene Services & Documentation were applicable to an audit for Approved Inspection Authorities for occupational hygiene. Twenty two or 84.6% of the respondents strongly agreed that the said elements were adequate for an occupational hygiene audit. Four or 15.4% of the respondents disagreed, responding that the proposed elements were not adequate for an audit of Approved Inspection Authorities for occupational hygiene. 6 Four of the 26 respondents indicated that the elements; Suppliers & Accommodation should be excluded from the proposed occupational hygiene audit. Twenty two or 84.6% of the respondents strongly agreed that audits are effective in the identification of poor quality work and the subsequent need for corrective measures. Forty two percent of the respondents agreed to the use of the four point scale applied by most of the CONCAWE member companies (Brussels), which was suggested for the proposed audit of the Approved Inspection Authorities for occupational hygiene. Two of the respondents preferred the use of the terms “comply” and “not comply” instead of a numerical rating or scoring mechanism. Two respondents stated that they preferred the use of a five point scale (numbers 1 – 5) as a scoring mechanism. Six of the respondents stated that they would use a different scoring mechanism but did not explain, or elaborate on their statement. Five respondents did not complete the section on the suggested scoring mechanism. On the subject of adequate scores the study found that 18 of the respondents suggested a score of not less than 80% (out of a possible 100%). The majority of respondents indicated that a score of less than 60% warranted corrective action from the Department of Labour or the Southern African Institute for Occupational Hygiene. The majority of respondents preferred the legal appointment of the Department of Labour as the body permitted and approved to audit the operational activities of Approved Inspection Authorities for occupational hygiene. From the results of the study the researcher concluded that a need exists for a formal auditing and scoring system for operational work of Approved Inspection Authorities for occupational hygiene. A proposed audit tool was designed and is appended.
Keywords: occupational hygiene; audit; inspection authorities